Design of cobalt‐iron complex sulfides grown on nickel foam modified by reduced graphene oxide as a highly effect bifunctional electrocatalyst for overall water splitting. (9th January 2022) - Zhang, Kai; Jiang, Pingping; Gu, Qian; Leng, Yan; Zhang, Pingbo; Li, Zhenhua; Li, Yuchao
Summary: Development of high‐authority and rich‐in‐crust bifunctional electrocatalysts for overall water splitting has a great significance of clean energy storage and conversion with both of the oxygen evolution reaction (OER) and hydrogen evolution reaction (HER). In this work, cobalt‐iron complex sulfides with the same metal molar ratio firmly grown on the surface of nickel foam modified by reduced graphene oxide (Co0.50 Fe0.50 S‐rGO@NF) was prepared and acted as a superior electrocatalyst for electrolyzing water. The same mole ratio of bimetallic‐cation doping can induce strong electron‐interaction between the complex sulfides and the surface of nickel foam carrier modified by reduced graphene oxide, which reduces the electronic adsorption energy required for HER and OER, as well as improves the electrocatalytic active area exposure. As a result, the optimal electrocatalyst of Co0.50 Fe0.50 S‐rGO@NF behaves excellent electrocatalytic performance with the overpotential of 189 mV @ η 20 mA·cm −2 in 1.0 M KOH solution for OER and the overpotential of 155 mV @ η 10 mA·cm −2 in 0.5 M H2 SO4 solution for HER, respectively. A self‐built conventional two‐electrode electrolytic cell by using Co0.50 Fe0.50 S‐rGO@NF as the anode and cathode presents lower voltages of 1.39 and 1.66 V to deliver the current density of 10 mA·cm −2 in 1.0 M KOH and 1.0 M PBS electrolytes, respectively. This study underlines the synergism of the bimetallic‐cation doping complex sulfides loaded on nickel foam modified by rGO for boosting the electrocatalytic activity of overall water splitting. Abstract : The manuscript entitled "Design of Cobalt‐Iron Complex Sulfides Grown on Nickel Foam Modified by Reduced Graphene Oxide as a Highly Effect Bifunctional Electrocatalyst for Overall Water Splitting" was original and the authors of this manuscript include Kai Zhang, Pingping Jiang*, Qian Gu, Yan Leng, Pingbo Zhang, Zhenhua Li and Yuchao Li. The novelty of this manuscript rests with that the as‐prepared novel Co0.50Fe0.50S‐rGO@NF exhibited lower overpotentials for OER and HER together with excellent stability and durability in both of the alkaline and acid electrolytes. This work still shows excellent electrocatalytic performance in overall water splitting experiment.